2012
DOI: 10.1093/annonc/mdr336
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of patupilone in patients with metastatic castration-resistant prostate cancer previously treated with docetaxel: Canadian Urologic Oncology Group study P07a

Abstract: Patupilone at 8 mg/m2 was tolerable, had antitumor activity, and was associated with symptomatic improvement in patients previously treated with docetaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The PSA response rate and PFS observed in our sagopilone study are comparable to those reported for ixabepilone and patupilone (Galsky et al , 2005; Hussain et al , 2005; Chi et al , 2012). Differences between these compounds are more evident in the toxicity profiles: neutropenia and neuropathy associated with ixabepilone (Galsky et al , 2005; Hussain et al , 2005), diarrhoea associated with patupilone (Chi et al , 2012), and neuropathy associated with sagopilone.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The PSA response rate and PFS observed in our sagopilone study are comparable to those reported for ixabepilone and patupilone (Galsky et al , 2005; Hussain et al , 2005; Chi et al , 2012). Differences between these compounds are more evident in the toxicity profiles: neutropenia and neuropathy associated with ixabepilone (Galsky et al , 2005; Hussain et al , 2005), diarrhoea associated with patupilone (Chi et al , 2012), and neuropathy associated with sagopilone.…”
Section: Discussionsupporting
confidence: 86%
“…Efforts have been directed towards evaluating the role of epothilones in metastatic CRPC, and to date two epothilones, ixabepilone and patupilone, have been investigated for the treatment of this disease (Galsky et al , 2005; Hussain et al , 2005, 2009; Chi et al , 2012). In a phase II study, weekly patupilone (2.5 mg m −2 ) showed minimal activity in patients with PC (Hussain et al , 2009), although response improved with 3-weekly patupilone (8 mg m −2 ) in a second phase II study (Chi et al , 2012). More robust activity was seen with ixabepilone, although this was not significantly different from that observed with docetaxel (Galsky et al , 2005; Hussain et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8) was approved for monotherapy against metastatic breast cancer by the FDA in 2007, and is currently in many trials from Phase I to Phase III against a variety of carcinomas. Although it reached Phase III trials with Novartis, epothilone B or patupilone was withdrawn from the Phase III level but it is currently in a number of Phase II trials under the auspices of Novartis, and recently, data from a recent Phase II trial was published demonstrating activity in prostate cancer [76]. Dehydelone (didehydroepothilone D) was in Phase II trials as late as 2008 (Fig.…”
Section: The Role Of Microorganisms In Drug Discoverymentioning
confidence: 99%
“…Importantly, patupilone is also not affected by common tumor resistance mechanisms, including β-tubulin mutation and overexpression of drug efflux pumps 4649. Its antitumor activity has been shown in several clinical trials with various tumor types, including prostate, ovarian, and colon cancers 5053…”
Section: Mechanisms Of Action Of Mbasmentioning
confidence: 99%